PEMBUATAN SITE PLAN RENCANA PEMBANGUNAN TANGKI SEPTIK SKALA INDIVIDUAL PEDESAAN DI KELURAHAN BUSOA - Ahmad Efendi; Agus Syafruddin (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
The limited availability of sanitation facilities and technical understanding among the community in Busoa Village poses a risk of contaminating clean water sources and threatening environmental health. This community service project aims to prepare a Site Plan Design Document (2D Plan Layout) for the construction of individual-scale septic tanks for 25 targeted households that comply with engineering standards. The methodology employed an engineering spatial mapping and two-dimensional site planning approach executed through three main stages: a GPS-based geotagging survey, draft digitization using CAD software, and participatory validation with residents and local government via Focus Group Discussions (FGD). This initiative successfully produced an A3-standardized 2D Site Plan Design Document in both hardcopy and softcopy formats. This output serves as a technical guideline for self-managed community sanitation arrangement and acts as a blueprint for local governments in planning settlement programs and distributing sustainable sanitation assistance